Quality assessment of frozen passion fruits (Research, Society and Development, 2020)
The objective of this work was to evaluate the microbiological quality and physical and chemical characteristics of frozen passion fruit pulp marketed in two supermarkets in the city of Machado/MG, in order to verify the adequacy of the product to the standards established by current legislation. The following analyzes were performed: coliforms at 35oC, Salmonella spp. research, mold and yeast count, pH, titratable acidity, soluble solids, total solids, total soluble sugars and color (L* value, hue angle and chroma). All passion fruit pulps analyzed presented values ​​below 0.3 NMP.g-1 for coliforms at 35°C, absence of Salmonella spp. in 25 g and yeast and mold count less than 5x10³ CFU.g-1, meeting ANVISA and MAPA microbiological standards for fruit pulp. Frozen passion fruit pulp marketed in supermarkets showed pH, titratable acidity, soluble solids and total solids within the identity and quality standards established by the current legislation for passion fruit pulp. The total soluble sugar content of frozen passion fruit pulp sold in supermarkets A and B were 4.69% and 3.79%, respectively. It is concluded that the frozen passion fruit pulp marketed in Machado/MG, are within the standards established by current legislation, indicating that the satisfactory hygienic-sanitary conditions of the product will not compromise the health and welfare of consumers and supermarkets showed good storage and marketing conditions.